The Effect Of English Language Speech Assistant (Elsa) To The Students’ Ability In Pronuncing English Verbs Of The Tenth Grade Sma Negeri 2 Pematang Siantar (International Journal of Education and Literature, 2025)
Pronunciation skills are fundamental in English language learning, especially in the correct articulation of regular past tense verbs. However, students often experience difficulties in accurately pronouncing such verbs due to the differences between English spelling and pronunciation. To address this issue, this study investigated the effect of the English Language Speech Assistant (ELSA) application on the pronunciation ability of tenth-grade students at SMA Negeri 2 Pematang Siantar. This research utilized a quantitative approach with a quasi-experimental design, involving 64 students divided equally into an experimental group (X-3) and a control group (X-9) selected through purposive sampling. The experimental group received instruction using the ELSA Speak application, while the control group was taught using conventional teaching methods. Data were collected through pre-tests and post-tests, then analysed using an independent sample t-test. The mean pre-test scores for the experimental and control groups were 50.34 and 50.21, respectively, while the mean post-test scores were 82.56 and 67.37. The t-test analysis revealed a significance value (2-tailed) of 0.000, which was lower than the significance level of 0.05 (0.000 < 0.05). Additionally, the computed t-value exceeded the t-table value (t-observed > t-table at df=62 and α=0.05), leading to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (H₀). This indicates that there is a significant difference between students taught using the ELSA Speak application and those taught using conventional methods. Based on the research findings, it can be concluded that the ELSA Speak application significantly improves students’ pronunciation abilities in pronouncing English regular past tense verbs.